Pengaruh Kualitas Pelayanan dan Biaya terhadap Kepuasan dan Loyalitas Pasien RSUD Kota Bogor - Adil, Adityawarman; Syamsun, Muhammad; Najib, Mukhamad (Jurnal Aplikasi Manajemen, 2016)
This study aims to determine the effect of quality of service and hospital's cost on patient satisfaction and loyalty. This study uses secondary data from hospital's document and primary data which collected through questionnaire's survey from the patients of Bogor Public Hospital, Indonesia. The method of analysis using Structural Equation Modeling (SEM) analysis. According to the method of Partial Least Square (PLS), service qualityand hospital's cost have significant impact on patient satisfaction. Service quality has significantlyÂ  impact to the patient loyalty, but the hospital's cost has no significant impact on patient loyalty. In addition, patient satisfaction significantly affect to the patient loyalty. According to this result, the hospital needs to improve the service quality and set the right cost in order to improve patient satisfaction and at the end, gain patient loyalty.